2006
DOI: 10.1007/s11596-006-0528-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of VEGF-C and VEGFR-3 expression in non-small cell lung cancer

Abstract: The relationship between vascular endothelial growth factor-C (VEGF-C)/vascular endothelial growth factor receptor 3 (VEGFR-3) expression and clinicopathologic features of the patients with non-small cell lung cancer (NSCLC) was investigated. The expression of VEGF-C and VEGFR-3 was assessed in 65 patients with NSCLC by immunohistochemistry. The significance of VEGF-C and VEGFR-3 expression was analyzed statistically. The results showed that VEGF-C and VEGFR-3 were highly expressed in cytoplasm and membrane in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 11 publications
5
37
1
Order By: Relevance
“…Several studies have reported VEGF-C expression in NSCLCs. [17][18][19][20][21][22] In addition, NSCLC patients with nodal metastasis revealed higher serum VEGF-C levels than those without. 31 However, the association of tumor-cell VEGF-C and nodal metastasis in NSCLCs is still debated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have reported VEGF-C expression in NSCLCs. [17][18][19][20][21][22] In addition, NSCLC patients with nodal metastasis revealed higher serum VEGF-C levels than those without. 31 However, the association of tumor-cell VEGF-C and nodal metastasis in NSCLCs is still debated.…”
Section: Discussionmentioning
confidence: 99%
“…31 However, the association of tumor-cell VEGF-C and nodal metastasis in NSCLCs is still debated. Three studies reported positive associations of tumor-cell VEGF-C status with nodal metastasis in NSCLCs 17,18 and micrometastasis in Stage I NSCLCs. 19 In contrast, three studies described no association of tumor-cell VEGF-C status with nodal metastasis in NSCLCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VEGF-C can also attract macrophages [124] that can alter the tumor microenvironment to promote invasion. Furthermore, some tumor cells also express VEGFR-3 and thus may benefit from autocrine signaling of VEGF-C or -D [121,[125][126][127][128][129]. Such autocrine signaling could help tumor cells home to lymphatics by guiding them in the direction of flow [42].…”
Section: Chronic Graft Rejectionmentioning
confidence: 99%